HUMAN CAPITAL INSTITUTE: FEATURES OF REPRODUCTION UNDER DIGITAL CONVERSION OF THE ECONOMICS - Tiutiunnykovа, Svitlana V.; Berveno, Oksana V.; Yaremenko, Valentyna G.; Yaremenko, Oleg L. (International Journal of Psychosocial Rehabilitation, 2020)
Modern knowledge on growth, employment and social development of a country and a society is mostly based on an institute of human capital. From the point of view of the current state structure, the consumption of large-scale public resources, ensuring the formation of a national institute of human capital, through a government-financed education system and thus long-term preservation of its values via the health and social care system are taken into account. Looking through the prism of the theory of the social choice, economics and labor market, the development of the human capital institution are logically determined as a top priority task in every modern political doctrine of social evolution under digital conversion of the economics. The purpose of the article was to systematize and critically study a human capital institute: features of its reproduction under digital conversion of the economics. During the research, the authors used theoretical and empirical methods, such as observation, tabular and graphical methods of data visualization, etc., allowing to achieve the set goal in a complex. The policy of development of the human capital institution and features of reproduction under digital conversion of the economics should be aimed at the young and adolescent generations, since they are the most competent in the widespread use of digital technologies. Therefore, the task is not only to help or organize, but also to form it as a substitute in the development of the labor market, capital, and funds. At the same time it should comply with terms and objectives of this development, and resources of the material and spiritual nature, considering that it forms not a flow, but human personality, and each has its own way, needs and attitude to the environment and other individuals.